MANAJEMEN STRATEGI KELESTARIAN KAWASAN DANAU MANINJAU (STUDI KASUS PENCEMARAN LINGKUNGAN OLEH KERAMBA JARING APUNG (KJA) DI NAGARI BAYUR) - Nengsih, Nelfia; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The Lake Maninjau area has historical, economic and social function that has important and strategic role for human development and development currently, Lake Maninjau is being heavily polluted due to the waste of Floating Net cage which has an impact on the environmental conditions in lake and economy of people in the lake area. The Environment agency that manages the environment certainly needs to apply strategic management to manage Lake Maninjau's sustainability to realize clean, sustainable, culture and sustainable lakes area. The purpose of this research is to know how management of Maninjau Lake sustainability strategy and what are the factors influencing management of Lake Maninjau Lake sustainability strategy. This research was conducted at Environment Department of Agam. The theory used in this research is Taufiqurokhman’s theory, there are some related indicators Management Strategy organization that is giving long-term direction, organizational effectiveness, prevent the emergence of problem, and involving member of organization. The research method used is descriptive qualitative research with data collection technique done through interview, observation and documentation. Selection of research informant using purposive sampling technique for Environment Department and accidental sampling technique for people and farmer of floating net cages. The result of this research is Management Strategy of manajement of Lake Maninjau preservation is still not maximum, because authority and activity in Lake Maninjau still unclear, people awareness still less in maintaining and taking care of environment in Lake Maninjau and budget to clean that lake is limited. Keywords: strategy management, environmental pollution, floating net cage